Acute tubulointerstitial nephritis in 10-year-old boy following severe acute respiratory syndrome coronavirus 2 infection - Aleksandra Sobieszczańska-Droździel; Adam Strzoda; Wojciech Sowiński (Termedia Publishing House, 2021)
The COVID-19 pandemic caused by coronavirus SARS-CoV-2 is currently a main public health problem worldwide. The clinical symptoms relate primarily to the respiratory system but may also involve multiple organs. The course of COVID-19 in children is usually mild, but in some cases may cause late complications, particularly the pediatric inflammatory multisystem syndrome (PIMS-TS). One of its symptoms may be acute kidney injury. We present a 10-year-old boy who developed nonspecific symptoms a few weeks after mild COVID-19, including weakness, weight loss, and polyuria. Clinical evaluation revealed acute renal failure secondary to acute tubulointerstitial nephritis (ATIN). Treatment with glucocorticoids resulted in rapid clinical and laboratory improvement. We hypothesize that the development of ATIN could be causally related to COVID-19 in an immune pathomechanism similar to PIMS-TS. The case provides new insights into possible complications of SARS-CoV-2 infection and indicates the need for renal follow-up after COVID-19.